Northern Sudan ivory market flourishes - Martin, Esmond (Pachyderm, 2005)
This article reviews a January-February 2005survey intended to assess the status of ivory markets in Omdurman and Khartoum. The author suggests ’ivory market in the Khartoum-Omdurman area of northrt sudan is one of the few in the world tht has expanded significantly since the mid-1990s’. He found the price craftsment paid for raw ivory had increased ’workhop owners and craftsmen pay USD 105/kg for a 2-5 kg tusk compared with USD 44/kg for a 5-10 kg tusk in 1997’. The number of craftsment has also increased during this same time period, about 150 craftsmen who carve both ivory and work were identified compared to about 100 in 1997. Jewellery and small figurines are the most common items made. The author noted 50 retail outlets who displayed over 11300 items made from tusks probably obtained from elephant poached since 1990. Accoding to Sudanese law this trade in new ivory is illegal ,and the author suggest that is ’threatening central African elephant populations’. The items are cheap compared with prices in other countires and nearly all the buyers are foreigners working in Sudan.